2021
DOI: 10.1007/s10096-021-04332-0
|View full text |Cite
|
Sign up to set email alerts
|

Human seroprevalence of Toscana virus and Sicilian phlebovirus in the southwest of Portugal

Abstract: Toscana virus (TOSV) is emergent in the Mediterranean region and responsible for outbreaks of encephalitis or meningoencephalitis. Sicilian phlebovirus (SFSV) cause epidemics of febrile illness during the summer. The aim of this study was to evaluate the presence of antibodies against TOSV and SFSV in humans in the southwest of Portugal. Neutralizing antibodies to TOSV and SFSV were respectively detected in 5.3% and 4.3% out of 400 human sera tested highlighting the need to increase public health awareness reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This was the first time that SFSV infection was linked to a symptomatic infection in this country. The presence of the virus in Portugal is corroborated by several seroprevalence studies which found antibodies in 4.3% (17/400) of the studied human population in Setúbal district, southwest of Portugal, and in domestic animals such as cats (2.2%, 8/367) and dogs (50.8%, 581/1160; 56.3%, 327/581) [59][60][61][62].…”
Section: Sicilian Phlebovirussupporting
confidence: 54%
See 1 more Smart Citation
“…This was the first time that SFSV infection was linked to a symptomatic infection in this country. The presence of the virus in Portugal is corroborated by several seroprevalence studies which found antibodies in 4.3% (17/400) of the studied human population in Setúbal district, southwest of Portugal, and in domestic animals such as cats (2.2%, 8/367) and dogs (50.8%, 581/1160; 56.3%, 327/581) [59][60][61][62].…”
Section: Sicilian Phlebovirussupporting
confidence: 54%
“…Three other patients presented serological evidence of previous contact with the virus [58]. Another recently published regional study (2022) involving only individuals from the Setúbal county, disclosed that out of 400 sera tested, 21 (5.3%) were positive for TOSV IgG [59].…”
Section: Toscana Phlebovirusmentioning
confidence: 95%
“…The seroprevalence of TOSV in people from Murcia is on the high end of the 2–37% and 0–26% range seroprevalences with ELISA or IFAT and VNT techniques, respectively, reported in other studies of Spain, Portugal, Italy and France (Amaro et al., 2011 ; Amodio et al., 2011 ; de Ory et al., 2009 ; Echevarría et al., 2003 ; Maia et al., 2021 ; Mendoza‐Montero et al., 1998 ), and lower than the 46% VNT positives in North African countries (Alkan et al., 2015 ) and the 77% ELISA positives reported among forestry workers in some areas in Italy (Valassina et al., 2003 ). Sandfly vectors are abundant in rural areas in Murcia (Muñoz et al., 2018 ; Risueño et al., 2017 ) and increasing TOSV seroprevalence with age in this study is compatible with increasing cumulative risk of infection, and the same relationship was reported in other studies (Cardeñosa et al., 2013 ; de Ory‐Manchón et al., 2007 ; Punda‐Polić et al., 2012 ; Sanbonmatsu‐Gámez et al., 2005 ; Terrosi et al., 2009 ).…”
Section: Discussionmentioning
confidence: 74%
“…To date, at least four phleboviruses are known to circulate in Portugal: TOSV with reported isolation and serological evidence in humans and serological evidence in cats and dogs; Massilia and Alcube viruses (Phlebovirus massiliaense and Phlebovirus alcubeense, respectively), isolated and detected, up to date, only in sand flies; and the SFSV recently associated with human disease in Portugal and detected in sera samples of humans, cats, and dogs [25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent study conducted to evaluate the presence of antibodies against TOSV and SFSV in a human population residing in the southwest of Portugal, seroprevalences of 5.3% and 4.3% were detected, respectively [ 32 ]. Nonetheless, phlebovirus infections are still neglected in the country.…”
Section: Introductionmentioning
confidence: 99%